PCaaD: Towards automated determination and exploitation of industrial systems. Issue 110 (November 2021) - Green, Benjamin; Derbyshire, Richard; Krotofil, Marina; Knowles, William; Prince, Daniel; Suri, Neeraj
Abstract: Over the last decade, Programmable Logic Controllers (PLCs) have been increasingly targeted by attackers to obtain control over industrial processes that support critical services. Such targeted attacks typically require detailed knowledge of system-specific attributes, including hardware configurations, adopted protocols, and PLC control-logic, i.e., process comprehension. The consensus from both academics and practitioners suggests stealthy process comprehension obtained from a PLC alone, to execute targeted attacks, is impractical. In contrast, we assert that current PLC programming practices open the door to a new vulnerability class, affording attackers an increased level of process comprehension. To support this, we propose the concept of Process Comprehension at a Distance (PCaaD), as a novel methodological and automatable approach towards the system-agnostic identification of PLC library functions. This leads to the targeted exfiltration of operational data, manipulation of control-logic behavior, and establishment of covert command and control channels through unused memory. We validate PCaaD on widely used PLCs through its practical application.